Fatigue investigation on crack problems in layered metal alloy materials - Cao, Yang (Nanyang Technological University, 2021)
3D printing for metal materials has been widely used in the aerospace field. Nickel base alloy such as Inconel 718 with SS316L is applied to the turbine of aero engine. However, when nickel-base superalloys are prepared by SLM technology, cracks are easy to occur along the interface of the two dissimilar materials. So far, the research work has not been done on how different shapes of the interface of layered metal alloy influence crack propagation and fatigue life of layered metal alloy. In the current study, low cycle fatigue (LCF) behaviours of the layered metal alloy materials are investigated using the Extended Finite Element Method (XFEM). The alloy Inconel 718 with SS316L is used as an example material for our study. The significant parameters affecting the crack propagation rate such as the crack orientation and ratio of elastic modular are studied. Moreover, it is concluded that the flat interface causes a larger crack propagation rate compared to the wavy interface of the model, which means that the wavy interface is more resistant to crack propagation and extension than the flat interface. Besides, through the parameter study of different ratios of elastic modular, it is found that the crack propagation will bend over to the part with lower elastic modulus in the layered metal alloy.